Water Budgets for Florida Dairy Farms - David R. Bray; Ray A. Bucklin; H. H. Van Horn; R. A. Nordstedt; Adelbert B. Bottcher; R. N. Gallaher; Carroll G. Chambliss; G. Kidder (EDIS)
Revised! Circular 1091, a 6-page fact sheet by D. R. Bray, R. A. Bucklin, H. H. Van Horn, R. A. Nordstedt, A. B. Bottcher, R. N. Gallaher, C. G. Chambliss, and G. Kidder, provides estimates of amounts of water commonly used for various purposes so that water use budgets for dairy farms can be developed on a per-cow and total-farm basis. Includes references. Published by the UF Department of Animal Science, May 2008.